Chiaroscuro : Renaissance woodcuts from the collections of Georg Baselitz and the Albertina, Vienna - Gnann, Achim; Ekserdjian, David; Foster, Michael; Royal Academy of Arts (Great Britain) (London : Royal Academy of Arts, 2014)
Traces the genesis and dissemination of chiaroscuro woodcuts in 16th-century Germany, Italy, and the Netherlands, with more than 130 examples including masterpieces by Cranach, Beccafumi, and Goltzius.
"The chiaroscuro woodcut was developed in Germany in the early 16th century. By printing from one or more colour blocks in addition to the customary line block, artists found that they could create a dramatic interplay of light and shade - chiaroscuro, the word that came to define the genre. They used its painterly qualities to create both independent works of art and reproductions of drawings and paintings by others. This handsome publication brings together more than 130 chairoscuro woodcuts from Germany, Italy and the Netherlands, documenting the fascinating history of the technique during its golden age. It is lavishly illustrated with some of the rarest and finest woodcuts from the collections of the painter Georg Baselitz and the Albertina museum of prints and drawings in Vienna, inclkuding masterpieces by such well-known artists as Lucas Cranach the Elder and the undisupted Italian master of the genre Ugo da Carpi." -- Publisher's description.
The chiaroscuro woodcut: an introduction / Achim Gnann -- Georg Baselitz and the collecting of prints / David Ekserdjian -- Catalogue. Beginnings: Lucas Cranach in Wittenburg and Hans Burgkmair in Augsburg ; Strasbourg: Hans Wechtlin and Hans Baldung Grien ; The chiaroscuro woodcut elsewhere in the German-speaking world ; Beginnings in Italy: Ugo da Carpi ; Ugo da Carpi's pupils and followers ; Domenico Beccafumi ; Cremona and Bologna ; Germany and the Netherlands in the second half of the sixteenth century ; Developments in Italy.
Catalog of the exhibition at Royal Academy of Arts, London, 15 March-8 June 2014.
Includes bibliographical references and index.
Keywords: Baselitz, Georg, -- 1938- -- Art collections -- Exhibitions; Graphische Sammlung Albertina -- Exhibitions; Wood-engraving, Renaissance -- Private collections -- Exhibitions; Wood-engraving, Renaissance -- Collectors and collecting -- Exhibitions; Chiaroscuro -- Private collections -- Exhibitions; Chiaroscuro -- Collectors and collecting -- Exhibitions